Enhancing consumer online engagement through consumer involvement: A case of airline and hospitality services in Malaysia - Leong, Mei Kei *; Syuhaily Osman,; Laily, P.; Sabri, M. F. (Growing Science, 2019)
Consumer online engagement has seen a sight of emerging attention by marketing literature, but how consumer involvement, with its dimensions (importance, pleasure, sign, risk consequence, and risk probability), is linked with consumer online engagement still requires additional empirical analysis especially in the context of airline and hospitality services. The purpose of this study is to examine the relationship between consumer involvement and its dimensions and consumer online engagement. The data are collected from the social media website and analyzed by using structural equation modelling through SPSS and Smart PLS 3.0 software. The findings imply that sign value was the major determinant of consumer online engagement. This indicates that marketers should acknowledge the importance of company’s symbolic value and design a suitable symbolic value to be parallel with the targeted consumers’ social status and personal images to increase consumer online engagement. Through examining the relationship among different variables, marketers could develop effective strategies to gain competitive advantages. The originality of this study lies within the research gap of the past researches on the antecedent of consumer online engagement. The antecedent considered is consumer involvement, suggested by previous researches.